Minority Dropouts in Higher Education: The Influence of Family Factors - Sengsouliya, Souksakhone; Vannasy, Vanmany (Indonesian Journal of Adult and Community Education, 2023)
According to existing literature, familial support has been shown to be a significant predictor of students’ success or failure in school. In this paper, we investigate family-related factors that contribute to minority students dropping out. A qualitative research approach was employed in this study, which involved 11 Hmong studentleavers as key interviewees. Participants were asked about their university education experiences and why they discontinued their studies. The data obtained from interviews were analyzed through qualitative content analysis. As the findings of the study indicate, four family-related factors were most prevalent in causing minority students to withdraw from their studies: family economic situation, parental attitudes, marriage/early parenthood, and home life situations. Future research in this area is strongly recommended.